2019
DOI: 10.1177/0972150918825400
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Validating a Scale to Assess Strategic Entrepreneurship Among Women: A Case of Jammu and Kashmir in India

Abstract: The combination of entrepreneurship and strategic management, called strategic entrepreneurship, is still in its infancy, as Hitt et al. proposed it in the year 2001. Since then researchers have continuously pushed their limits to explore it on different fronts and domains. But, so far, a mutual consent on what actually constitutes it has not been achieved. In developing nations like India, this concept presents huge opportunities for researchers to explore it on different dimensions and domains. Specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…SMEs' performance during the economic crisis was primarily examined in relation to their entrepreneurial attitude, innovation, strategic resource management, and competitive advantage. A framework was developed by Siddiqui and Jan [26] for the evaluation of SE in female-owned businesses in India. They found that innovativeness, networking, smart resource management, entrepreneurial culture and leadership, and entrepreneurial mindset all had an impact on SE.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…SMEs' performance during the economic crisis was primarily examined in relation to their entrepreneurial attitude, innovation, strategic resource management, and competitive advantage. A framework was developed by Siddiqui and Jan [26] for the evaluation of SE in female-owned businesses in India. They found that innovativeness, networking, smart resource management, entrepreneurial culture and leadership, and entrepreneurial mindset all had an impact on SE.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The finding of Siadat and Naeiji (2019) demonstrated that these five dimensions had positive effects on knowledge-based firms' competitiveness. Siddiqui and Jan (2019) developed a framework to evaluate female entrepreneurship's strategic entrepreneurship in the Indian context. They found that innovativeness, entrepreneurial leadership, entrepreneurial culture, strategic management of resources, entrepreneurial mindset, and networking are the most significant factors in supporting strategic entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There has been increasing attention among the researchers on women entrepreneurship in India since the economic liberalization and globalization. It is believed that the engendering of more women entrepreneurs can lead to economic growth in the country (Siddiqui & Jan, 2019). Female entrepreneurs are mostly found in the informal sector in India (Ghani, Kerr, & O’Connell, 2013a; Williams & Gurtoo, 2011).…”
Section: Review Of Literaturementioning
confidence: 99%